7x+2=6x+1

Simple and best practice solution for 7x+2=6x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+2=6x+1 equation:


Simplifying
7x + 2 = 6x + 1

Reorder the terms:
2 + 7x = 6x + 1

Reorder the terms:
2 + 7x = 1 + 6x

Solving
2 + 7x = 1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
2 + 7x + -6x = 1 + 6x + -6x

Combine like terms: 7x + -6x = 1x
2 + 1x = 1 + 6x + -6x

Combine like terms: 6x + -6x = 0
2 + 1x = 1 + 0
2 + 1x = 1

Add '-2' to each side of the equation.
2 + -2 + 1x = 1 + -2

Combine like terms: 2 + -2 = 0
0 + 1x = 1 + -2
1x = 1 + -2

Combine like terms: 1 + -2 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| 4q+6=90 | | 3h^2+7hk+2k^2= | | 10x-11=2x+10 | | v=(3.14)(144)(14) | | (5u-6)(1+u)=0 | | 4x-2(12)=3(-3)+8 | | 10t-3t=42 | | 5z-4-3z+2=0 | | -2[x+3]=5 | | -4(7x-7)=-84 | | 3+7x=-33+x | | 5a-11=3a-7 | | 4x+5=65is[4x+5] | | 11(C-3)=5(C+3) | | 9(z+2)=36 | | 9x=10+-5x | | 8x+4y= -52 | | 25x+35y+70= | | r^2+r-2=0 | | 2*(a+5)=15 | | y-3=0(x-3) | | (6-4i)(-2-i)= | | 5z-11-2+3=0 | | X^5+16x^4-10x^3-x^2+5x+22=0 | | T=4w-2 | | y-5=0(x+5) | | x+4/7=3/7 | | v=(3.14)(16)(9) | | -9=-x-22x-3 | | 4+55x=44x+12 | | 3*Y-5+Y=31 | | 5x=25-7 |

Equations solver categories